An appraisal of medical institutions and medical professionals in Nigeria (1995)
This paper takes a critical look at the medical institutions and medical professionals in our country. It assesses how well |Nigerians are being served by them, and concludeds that some changes are called for in the quality , quantity and patterns of health care delivery system in this country. The paper ended with a few sugestions and recommendations.